KONDISI SERANGAN SERANGGA HAMA PADA BIBIT BAKAU (Rhizopora apiculata Bl) DI PUP PT. BINA OVIVIPARI SEMESTA KALIMANTAN BARAT - Utari, Veny; Ekyastuti, Wiwik; Oramahi, H A (Universitas Tanjungpura, 2017)
Condition of mangrove seeds attacked by pest insect and their level of destruction at PUP PT. BIOS are inidetified until now. The purpose of this study was to identify the spesies of insect that attacked mangrove seeds and to investigate their level of destruction at PT. BIOS West Kalimantan. This study was conducted for 4 weeks at PT. BIOS, Batu Ampar sub-district, Kubu raya regency. Survey method was applied for collecting data of research, specifically employing direct observation in research setting toward: 1) destruction level of mangrove seeds attackedby pest insect, 2) signs on plant, and 3) types of pest insect that attacked mangrove seeds. The collected data was analyzed by calculating the percentage on plant attacked by pest insect at each PUP, level of destruction at each PUP, level of destruction at all PUP, and frequency of pest insect attacked at each PUP. The findings indicate that 4 types of pest insect has attacked the mangrove (Rhizophora apiculata) seeds at PT. BIOS, Batu Ampar sub-district, Kubu raya regency and they consisted of 3 ordo and 4 families, distinctively Polistes sp, Sexsava sp, Orgyia postica, and Dasychira inclusa. They study revealed that the level of destruction on mangrove (Rhizophora apiculata) seeds at PT. BIOS, Batu Ampar sub-district, Kubu raya regency was categorized as low to average (15% to 40,57%) as well. Keywords: insect, mangrove seeds (Rhizophora apiculata Bl)